Behavioural and neuroimaging correlates of impaired self-awareness of hypo- and hyperkinesia in Parkinson's disease. (September 2016) - Maier, Franziska; Williamson, Kim L.; Tahmasian, Masoud; Rochhausen, Luisa; Ellereit, Anna L.; Prigatano, George P.; Kracht, Lutz; Tang, Chris C.; Herz, Damian M.; Fink, Gereon R.; Timmermann, Lars; Eggers, Carsten
Abstract: Introduction: Anosognosia or impaired self-awareness of motor symptoms (ISAm) has been rarely investigated in Parkinson's disease (PD). We here studied the relationship between ISAm during periods with and without dopaminergic medication (ON- and OFF-state), and clinical, neuropsychological, and neuroimaging data to further elucidate behavioural aspects and the neurobiological underpinnings of ISAm. Methods: Thirty-one right-handed, non-demented, non-depressed PD patients were included. ISAm was evaluated using a recently developed scale that assesses awareness of dyskinesia, resting tremor, and bradykinesia. The test was applied during both ON- and OFF-states. Multiple correlation analyses between ISAm and behavioural data were conducted. In addition, imaging of glucose metabolism using 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) was performed to investigate the neural basis of ISAm. A multiple regression approach was applied to investigate metabolism alterations related to ISAm. Results: In the OFF-state, higher ISAm was associated with left-sided disease onset, older age, and shorter disease duration. Concerning FDG-PET data, there was a significant negative correlation between higher OFF-state ISAm and decreased glucose metabolism in the right inferior frontal gyrus (IFG). In the ON-state, ISAm was not significantly correlated with clinical or behavioural data. However, there was a significant correlation between higher ISAm and an increased metabolism in the bilateral medial frontal gyrus, left IFG, right superior frontal gyrus and right precentral gyrus. Conclusion: The results support the role of the right hemisphere in awareness of motor symptoms in the OFF-state. In the ON-state, dopaminergic medication and dyskinesia influence ISAm and relate to metabolism changes in bilateral frontal regions.